2010
DOI: 10.1002/polb.22184
|View full text |Cite
|
Sign up to set email alerts
|

Reverse mode operation polymer dispersed liquid crystal with a positive dielectric anisotropy liquid crystal

Abstract: The development of electrically activated chromogenic materials is important for their potential applications in smart windows. Several previous works have reported on reverse mode operation polymer dispersed liquid crystals (PDLCs) based on negative dielectric anisotropy liquid crystals. They have a transparent OFF state, which turns opaque after the application of a suitable external electric field. Nevertheless, these devices have some limitations such as the use of large amount of expensive liquid crystals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…This is described as the random orientation of nematic liquid crystal in all directions. [18,19] The images for R-PDLC device doped with surfactant are shown in Figure 2D. Figure 2D showed the major part of the device as black.…”
Section: Results and Discussion Surface Morphologymentioning
confidence: 99%
See 2 more Smart Citations
“…This is described as the random orientation of nematic liquid crystal in all directions. [18,19] The images for R-PDLC device doped with surfactant are shown in Figure 2D. Figure 2D showed the major part of the device as black.…”
Section: Results and Discussion Surface Morphologymentioning
confidence: 99%
“…The darker state under the polarised optical films is defined as the vertical and grey the tilted arrangement of LC molecules towards the light. [18,19] It can be stated as the R-PDLC devices filled with Brij30 has homeotropic liquid crystal molecular orientation. The reason for getting homeotropic alignment or vertical orientation in the simply surfactant-doped devices could be the decrease in surface free energy of the device filled with surfactant.…”
Section: Results and Discussion Surface Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have reported examples of reverse-mode PDLC films obtained by modification of the polymer surface energy, [6] by functionalising the LC/polymer matrix interface, [7] by using dualfrequency addressable LC, [8] by means of rough surfaces [9,10] or by increasing the LC content. [11] Unfortunately, the existing process to prepare reverse-mode PDLC films was complex and expensive, which resulted in restricted in many fields for its further applications.…”
Section: Introductionmentioning
confidence: 99%
“…20 Therefore to overcome to the hitches, different techniques for getting reverse mode PDLCs with HA of LCs have been proposed using positive and negative dielectric anisotropic LCs. 21,22 Alteration of glass surface by polyvinyl butyral layer, 23 photoalignment, 24 cetyltrimethylammonium bromide coatings on indium tin oxide (ITO) surfaces, 25 rough surfaces for orientational control, 13,26 and doping of ferromagnetic nanoparticles (NPs) 27 are few other reported techniques for reverse mode PDLCs. HA of LC molecules was also achieved by utilizing the polysulfone polymer 28 and surfactant (ionic and nonionic) 7 in PDLC mixtures.…”
Section: Introductionmentioning
confidence: 99%